Program Pendampingan Masyarakat Pada Budidaya Kepiting Bakau (Scylla Spp.) Metode Pagar Bambu Tancap Kombinasi Jaring Pada Lahan Mangrove di Desa Sekaroh Kabupaten Lombok Timur Nusa Tenggara Barat - Alis Mukhlis; Bagus Dwi Hari Setyono; I Komang Damar Jaya (Universitas Mataram, 2022)
Mud crab (Scylla sp.) is a fishery commodity that has high economic value and is currently in great demand by local and foreign markets. Mud crab cultivation is relatively easy to do because of its resistance to changes in environmental conditions and lack of water. Coastal communities are one of the groups of people who are vulnerable to losing their livelihoods due to climate change, so they need to be empowered through the development of alternative businesses, namely mangrove crab cultivation by utilizing unproductive marginal lands such as mangrove land. On the other hand, mangroves have strategic value because of their role as carbon sinks in the air so that they can slow down the process of global warming. Until now, the role of coastal communities in mangroves is generally limited to the rehabilitation and preservation of mangroves, but not many people use it directly for fishery activities to improve the household economy. Community assistance activities regarding the cultivation of mangrove crabs using a combination of bamboo and net fence (kombuja) involving the coastal community of Sekaroh Village, Jerowaru District, East Lombok Regency, West Nusa Tenggara Province have been carried out. The results showed that there was a significant increase in the economic income of the target community accompanied by an increase in mangrove land management for mangrove crab cultivation activities based on environmental sustainability. This model is considered feasible to be developed and adopted by other coastal communities as a profitable alternative business while increasing public awareness of mangroves. This activity is a collaboration between the University of Mataram and the Commonwealth Scientific and Industrial Research Organization (CSIRO) of Australian Government.